1997
DOI: 10.1046/j.1365-2133.1997.19612035.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal naevi associated with trichilemmal cysts and chromosomal mosaicism

Abstract: We present the case of a 29-year-old woman who has had a widespread epidermal naevus since birth, located on the left side of her body, upon which multiple trichilemmal cysts developed several years later. The karyotype of peripheral blood lymphocytes revealed chromosomal mosaicism 46, XX, t (1;9) (p36:q34). The possible pathogenic mechanisms include paracrinopathy, germinal or somatic mutation in the multipotential embryo cells, or a combination of the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The abundance of sebaceous glands in the upper dermis and of apocrine glands suggested the diagnosis of a sebaceous nevus. A literature research finally revealed another 5 cases very similar to ours [2,3,4,5]. Leppard [2] described a 25-year-old patient with unilateral systematized warty lesions since birth that developed from age 10 on lumps that were found to be trichilemmal cysts in histopathology.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The abundance of sebaceous glands in the upper dermis and of apocrine glands suggested the diagnosis of a sebaceous nevus. A literature research finally revealed another 5 cases very similar to ours [2,3,4,5]. Leppard [2] described a 25-year-old patient with unilateral systematized warty lesions since birth that developed from age 10 on lumps that were found to be trichilemmal cysts in histopathology.…”
Section: Discussionsupporting
confidence: 64%
“…A case from Spain described an epidermal nevus with multiple small, milia-like trichilemmal cysts [3]. Another case of multiple trichilemmal cysts was even shown to have a mosaicism involving a translocation of chromosomes 1p and 9q [4], the impact of which remained unclear [5]. Multiple trichilemmal cysts in linear arrangement on the scalp were seen in a patient with type 2 segmental glomangiomatosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of cases where trichilemmal cyst could have been associated with epidermal nevi or comedo nevus 6,7 . The pathogenesis of these lesions suggested that they may arise from paracrinopathy or from germinal or somatic mutations in the multipotent embryo cells, or a combination of the two 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an organoid naevus combining filiform hyperkeratoses and trichilemmal cysts in Blaschko‐linear distribution has been delineated as a distinct entity 1 . The authors provided evidence that the same rare type of naevus had been described in a few previous instances without perceiving its originality 2–5 . Here, we would like to point out the so‐called naevus trichilemmocysticus or trichilemmal cyst naevus by reporting the first paediatric case.…”
mentioning
confidence: 88%